Analisis Visual Pada Poster Promosi Film Trilogi Batman - Ashari, Aldy Muhamad; Rochmawati, Irma (Fakultas Desain Universitas Komputer Indonesia, 2022)
A poster is a medium for delivering messages and information to the public that has been used for a long time following its interests, including in the promotion of a film. In promoting a film that will be shown, a promotional poster for the film will certainly greatly make the film to be shown more recognizable and at the same time as the 'face' of the film. This study examines the visual signs and elements displayed on promotional posters for Christopher Nolan's Batman trilogy, The Dark Knight Trilogy, which is the most successful Batman film in terms of income and awards. In the promotional poster for this film, there is an impression and a meaning that has a relationship with the film and not only as a mere aesthetic beauty in the poster's appearance. Ferdinand De Saussure's semiology is used as a research method to help researchers examine the visual elements and signs in this promotional poster. Semiology is the study of a sign, signifier, and signified and the relationship between these signs based on conventions in society. The results of this study found signs related to the film and the visual of the poster was made more than the reference to the movie scene.